Digestibilidade e desempenho de tilápias do Nilo (Oreochromis niloticus) utilizando farinha de penas submetida a diferentes tecnologias de produção - Xavier, Tadeu Orlandi (2015)
Two experiments were conducted to determine the apparent digestibility coefficients of energy and nutrients as well as apparent absorption coefficients of essential and nonessential amino acids of feather meal and the productive performance of juvenile tilapia fed feather meal submitted to different pressures and different times during the hydrolysis process. In the first experiment, 240 juveniles of Nile tilapia (24.53 ± 3.11 g), were distributed into eight fiberglass tanks of 200 liters each. A reference diet and eight test-diets were elaborated. A completely randomized design in a 2 x 4 factorial arrangement composed by feather meal subjected to two pressures (2.5 and 3.5 kgf/cm²) and four cooking times (10, 20, 30 and 40 minutes), respectively, was used. Except for leucine, glutamic acid, alanine, cystine, glycine, and tyrosine, significant interaction for apparent digestibility coefficients of crude protein gross energy and apparent absorption coefficients of amino acids were observed; where higher apparent digestibility coefficients and apparent absorption coefficients in feather meal submitted to hydrolysis during 20 minutes at 3.5 kgf /cm ² were observed. In the second experiment, during 50 days, 400 fish (6.90 ± 0.20 g), were distributed to 16-500 L plastic aquaria. Four extruded diets with 10% of feather meal were elaborated. A complete randomized design in a 2 x 2 factorial arrangement, composed of two pressures (2.5 and 3.5 kgf/cm²) and two cooking times (20 and 30 minutes) of feather meal was used. No significant differences on weight gain, feed conversion, protein efficiency rate, protein retention and body composition of the fish were observed. It was concluded that considering growth performance, higher apparent digestibility coefficients and apparent absorption coefficients is obtained in feather meal submitted to 20 minutes at 3.5 kgf/cm² during hydrolysis, what is recommended in diets for juvenile Nile tilapia.